Associations between the aetiology of preterm birth and mortality and neurodevelopment up to 11 years - Grönroos Linda; Rautava Päivi; Setänen Sirkku; Nyman Anna; Ekholm Eeva; Lehtonen Liisa; Ylijoki Milla; PIPARI Study Grp (Wiley-Blackwell Publishing Ltd., 2025)
Aim: To investigate how the aetiology of very preterm birth/very low birth weight is associated with mortality and later neurodevelopmental outcomes.
Methods: Very preterm/very low-birth weight singletons were categorised based on the aetiology of preterm birth: spontaneous preterm birth (n = 47, 28.1%), preterm premature rupture of membranes (n = 56, 33.5%) or placental vascular pathology (n = 64, 38.3%). Mortality, cerebral palsy, severe cognitive impairment by 11 years of age (<2SD) and mean full-scale intelligence quotient at 11 years were studied in association with birth aetiology.
Results: There was no difference in mortality or rate of cerebral palsy according to birth aetiologies. The rate of severe cognitive impairment was lower (4.9% vs. 15.3%) in the preterm premature rupture of the membrane group in comparison to the placental vascular pathology group (OR 0.2, 95% CI 0.03-0.9, adjusted for gestational age). At 11 years, there was no statistically significant difference in the mean full-scale intelligence quotient.
Conclusion: Placental vascular pathology, as the aetiology of very preterm birth/very low birth weight, is associated with a higher rate of severe cognitive impairments in comparison to preterm premature rupture of membranes, although there was no difference in the mean full-scale intelligence quotient at 11 years. The aetiology of very preterm birth/very low birth weight was not associated with mortality or the rate of cerebral palsy.
Keywords: PPROM; cognitive outcome; neurodevelopment; pre-eclampsia; very preterm birth.